Experimental investigation and metallographic characterization of fiber laser beam welding of Ti-6Al-4V alloy using response surface method. (August 2017) - Kumar, Chandan; Das, Manas; Paul, C.P.; Singh, B.
Abstract: In the present study, experimental investigations of fiber-laser-beam-welding of 5 mm thick Ti-6Al-4V alloy are carried out based on statistical design of experiments. The relationship between the process parameters such as welding power, welding speed, and defocused position of the laser beam with the output responses such as width of the fusion zone, size of the heat affected zone, and fusion zone area are established in terms of regression models. Also, the most significant process parameters and their optimum ranges are identified and their percentage contributions on output responses are calculated. It is observed that welding power and speed plays the major role for full penetration welding. Also, welding power shows direct effect whereas welding speed shows the inverse effect on the output responses. The bead geometry is influenced by the defocused position of the laser beam due to the change in power density on the workpiece surface. However, overall fusion zone area is unaffected. Mechanical characterization of the welded samples such as microstructural analysis, hardness, and tensile tests are conducted. It is noticed that the hardness value of the FZ is higher than the HAZ and BM zone due to the difference in cooling rate during welding which promotes the formation of α′ martensitic phase in the FZ. Also, an average hardness value in the FZ is compared for two different defocusing positions (i.e. 1 and 2 mm). It is found that hardness value is higher for 1 mm defocused position than 2 mm due the decrement in grain size below a critical range at 2 mm defocused position. The ultimate tensile strength and % elongation of the welded samples are degraded as compared to BM which can be further improved by post heat treatment. Highlights: Fiber LBW experiments are conducted on 5 mm thick Ti-6Al-4V alloy. Three process parameters i.e. LBW power, speed, defocused position are considered. Statistical DOE is carried out to identify the most significant process parameters. EDX analysis along the weld line confirms effectiveness of shielding gas. The metallographic features are studied using FESEM and optical microscope.